The Next green revolution: essential steps to a healthy, sustainable agriculture - Horne, James E.; McDermott, Maura (New Delhi : Atlantic Pub., 2001)
The next green revolution is an accessible, practical introduction to sustainable agriculture: what it means and why it is needed. The first book to synthesize the goals of sustainable agriculture into eight comprehensive steps, this essential volume examines the far-reaching problems inherent in our current agricultural system and introduces you to an alternative system that gives more consideration to future generations. The next generation revolution is a well-researched introduction to the field, written with a minimum of jargon.
Include bibliographical reference and index.
Keywords: Agriculture-industrial; Agriculture-green revolution